Screening of six UGT enzyme activities in human liver microsomes using liquid chromatography/triple quadrupole mass spectrometry. (9th October 2014) - Joo, Jeongmin; Lee, Boram; Lee, Taeho; Liu, Kwang‐Hyeon
<x xml:space="preserve">Abstract</x> RATIONALE Uridine 5'‐diphosphoglucuronosyltransferase (UGT) enzymes are essential for the clearance of many drugs; however, altered UGT activity is a potential cause of adverse drug‐drug interactions (DDI). The early detection of potential DDI is an important aspect of drug discovery that has led to the development of new screening methods for drug interactions. We developed a screening method for the simultaneous evaluation of six human liver UGT enzyme activites using in vitro cocktail incubation and tandem mass spectrometry. METHODS The two in vitro cocktail doses were developed to minimize drug interactions among substrates. The method is based on liquid chromatography/tandem mass spectrometry (LC/MS/MS). Electrospray ionization (ESI) in both positive and negative modes was used to quantify the metabolites and the diagnostic loss of the glucuronosyl moiety to form the aglycone product was estimated using the selected reaction monitoring (SRM) mode. RESULTS The method was validated by comparing inhibition data obtained from the incubation of each individual probe substrate alone with data from the cocktail method. The intra‐ and inter‐day accuracy and precision data for the six UGT metabolites ranged from 92.2 to 100.3% and less than 15.2%, respectively. The IC50 values showed no significant differences between individual and cocktail incubations. CONCLUSIONS As a screening technique for inhibitory interactions of these six human liver UGT enzymes, this method will be useful for advancing mechanistic understanding of drug interactions. Copyright © 2014 John Wiley & Sons, Ltd.